A storytelling intervention reduces childhood caries risk behaviors among American Indian and Alaska Native mothers in Northern California. (23rd April 2019) - Heaton, Brenda; Crawford, Andrew J.; Wimsatt, Maureen A.; Henshaw, Michelle; Riedy, Christine A.; Barker, Judith C.; Garcia, Raul I.
Abstract: Objectives: To evaluate a storytelling intervention targeting the oral health beliefs, knowledge, and behaviors of AIAN pregnant women and mothers. Methods: Fifty‐three adult AIAN women from three tribal communities in Northern California participated. The intervention story delivered oral health messaging using a traditional storytelling format. The effect of the intervention on self‐reported oral health behaviors, dental knowledge, and beliefs was assessed using a pretest‐posttest design, with an additional six‐month follow‐up. Tests of repeated measures using Generalized Linear Models were conducted to assess changes in oral health knowledge, beliefs, and behaviors. Results: Knowledge and beliefs significantly increased as a result of the intervention and persisted after six months. A consistent, significant increase in positive oral health behaviors from baseline to six‐months was also observed. Conclusions: The results of this intervention study suggest promise for traditional storytelling to increase oral health‐related knowledge, beliefs, and behaviors among self‐identified AIAN pregnant women and mothers.